Cerkvenoslovanska ostalina na Slovenskem - Babič, Vanda (Slavistična revija, 2012)
The Hagiography of St. Gregory, Pope of Rome is the eighth text in the Codex Suprasliensis, the largest Old Church Slavic Cyrillic monument from 10th-11th centuries. In Kopitar's bequest, now part of the Manuscript Collection of the National and University Library (NUK) in Ljubljana, the first 118 folios of a menology-ecclesiastic readings for the month of March - are preserved under the callnumber Cod. Kop. 2. The first part of the collection consists of nineteen texts of which seventeen are hagiographies of Orthodox saints, the other two arean adoration and a prayer. The Hagiography of St. Gregory, Pope of Rome, differs from most hagiographies, as it does not describe the martyrdom of a saint but rather his saintly life and/or his legendary positive characteristics-compassion and generosity.
Keywords: 10./11. st.; cerkvena berila; cirilski spomeniki; Codex Suprasliensis; cyrillic manuscripts; hagiografije; Hagiography of St. Gregory; menologij; menology; Old Church Slavic language; ortodox hagiography; pravoslavje; Retko's Codex; Retkov zbornik; rokopisi; Rokopisna zbirka NUK; stara cerkvena slovanščina; Supraseljski zbornik; Žitje sv. Gregorija